Community-based voluntary counseling and testing services in rural communities of Chiang Mai Province, northern Thailand - Surinda Kawichai (2018)
Between September, 2002 to May, 2003, we implemented community-based HIV Voluntary Counseling and Testing (VCT) services in four rural areas of Chiang Mai Province. The services included providing HIV/AIDS education and free mobile VCT using rapid testing with same day results. Overall, 427 villagers came for VCT (testers) and consented to be interviewed. HIV prevalence among testers was 4.9%, range from 1.1 to 8.4% by area. 'It is free' and/or 'convenient' were the most frequently cited factors that motivated them to get tested (72%) from our mobile VCT. Rural residents came for VCT when logistical barriers were removed. HIV prevalence among testers in some areas was high. Without extending HIV prevention efforts to population segments with less access to health care, the HIV problem in Thailand may re-emerge. Convenient and low-cost VCT may prove crucial for containing this HIV epidemic. © 2007 Springer Science+Business Media, LLC.